Faktorer som påverkar sockerförlusten vid lagring av sockerbetor - Martinsson, Ulrika (2011)
This thesis is a part of the project "Sustainable harvesting and storage of sugar beets, more sugar to practice". The work has included a large part of practical experimental work with weight measurement, graduation and storage planning. The aim of the project is to be able to see whether the cultivars react differently in different storage conditions. The project has included storage under controlled conditions to give as accurate results as possible. To be able to mimic the farmers own preconditions the samples was harvested with a conventional Holmer. This project has two parts, one concerning the nature, time and temperature on storage where a number of different cultivars where investigated during three different recording times, two different temperatures and controlled in a controlled environment. The second part examines the influence of humidity on sugar content. These samples were repeatedly moisturized during storage. Even these samples were harvested with the farmer's own harvesting equipment. The experiments of cultivars, time and temperature took place on two different sites, the first at Wragerup outside Malmö, Sweden and the other at Hviderup outside Eslöv, Sweden. These sites are selected since both sites have had problems with the storage of beet in clamps. The results also showed that there were differences between the sites when the figures were statistically analysed. In order to get the most secure results of lost sugar concentration, control samples were sent from all varieties directly to the biochemistry laboratory Agri in Örtofta for analysis. These values are then used as a control figure to determine the purity, weight and sugar content. In the experiments regarding humidity beets were picked randomly from the clamp and then stored under controlled forms in a long-term storage. In both studies sprouts on the beets and mold on the beets were graded. The results showed that the highest share of moisturized samples developed sprouts while the samples that had been dry during the whole storage time had the highest share of mold on the surface.